An evaluation of incentive policy effects on solar power plant cost analysis: a comparative case study approach - Erdem, Murat (Pergamon-Elsevier Science Ltd, 2025)
This study examines the economic feasibility of solar power plants and the renewable energy support mechanisms in Konya province, a region renowned for its high solar energy potential and leadership in solar energy investments in Turkey. The research evaluates the positive and negative effects of these mechanisms in Turkey from the perspective of investors, using practical examples. Although the analysis focuses on a region in Turkey, the findings and recommendations hold relevance for developing countries that are significantly affected by exchange rate fluctuations and inflation. The installation cost of a 1 MW solar power plant (SPP) is USD 864,517. The analysis spans a range of scenarios with different starting dates, extending up to December 31, 2024. Between 2015 and 2024, the total annual incentives provided to investors are calculated as follows: 726 cents USD/ kWh, 653.4 cents USD/kWh, 580.05 cents USD/kWh, 508.2 cents USD/kWh, 435.6 cents USD/kWh, 363 cents USD/kWh, 290 cents USD/kWh, 217.8 cents USD/kWh, 136.74 cents USD/kWh, and 59.4 cents USD/kWh, respectively. To achieve a payback period for solar power plants between 5 and 8 years, the incentive rate should be set between 15 cents USD/kWh and 20 cents USD/kWh. Accordingly, to enhance the sustainability and predictability of renewable energy investments, it is recommended to either remove or increase the upper limit applied within the incentive mechanism. Additionally, it is suggested that the denominators for PPI, CPI, and exchange rates in the mathematical formula be adjusted to incorporate historical data from earlier periods.
Keywords: Renewable energy; Solar power plant; Energy economics; Incentive programs